Marked seasonality of aerobic anoxygenic phototrophic bacteria in the coastal NW Mediterranean Sea as revealed by cell abundance, pigment concentration and pyrosequencing of pufM gene. (17th October 2013) - Ferrera, Isabel; Borrego, Carles M.; Salazar, Guillem; Gasol, Josep M.
Summary The abundance and diversity of aerobic anoxygenic phototrophs (AAPs) were studied for a year cycle at the Blanes Bay Microbial Observatory (NW Mediterranean) and their potential links to an array of environmental variables were explored. Cell numbers were low in winter and peaked in summer, showing a marked seasonality that positively correlated with day length and light at the surface. Bacteriochlorophyll a concentration, their light‐harvesting pigment, was only detected between April and October, and pigment cell quota showed large variations during this period. Pyrosequencing analysis of the pufM gene revealed that the most abundant operational taxonomic units (OTUs) were affiliated to phylogroup K (Gammaproteobacteria) and uncultured phylogroup C, although they were outnumbered by alphaproteobacterial OTUs in spring. Overall, richness was higher in winter than in summer, showing an opposite trend to abundance and day length. Clustering of samples by multivariate analyses showed a clear seasonality that suggests a succession of different AAP subpopulations over time. Temperature, chlorophyll a and day length were the environmental drivers that best explained the distribution of AAP assemblages. These results indicate that AAP bacteria are highly dynamic and undergo seasonal variations in diversity and abundance mostly dictated by environmental conditions as exemplified by light availability.